2021
DOI: 10.1155/2021/5546623
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Depression with Elder Abuse among Institutionalized Older Persons in Kathmandu Valley, Nepal

Abstract: Background. To identify the association between elderly abuse and depression among elderly living in old age homes of Kathmandu Valley, Nepal. Materials and Methods. A cross-sectional study was carried out in 5 old age homes of Kathmandu Valley, Nepal. The Geriatric Mistreatment Scale and the Geriatric Depression Scale were used to collect information from 220 elderly aged 65 or above, and face-to-face interviews were conducted. Bivariate and multivariate logistic regression analyses were carried out to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“… 75 Nevertheless, a recent study in Nepal has reported that neglect and economical abuse significantly increase the risk of geriatric depression. 76 In concordance with earlier research, 24 the current study has also found significantly increased odds of depression in women who are victims of abuse. Further, in this study, a significant association of elder abuse and place of residence on geriatric depression has been observed in the regression model with interaction analysis.…”
Section: Discussionsupporting
confidence: 91%
“… 75 Nevertheless, a recent study in Nepal has reported that neglect and economical abuse significantly increase the risk of geriatric depression. 76 In concordance with earlier research, 24 the current study has also found significantly increased odds of depression in women who are victims of abuse. Further, in this study, a significant association of elder abuse and place of residence on geriatric depression has been observed in the regression model with interaction analysis.…”
Section: Discussionsupporting
confidence: 91%
“…According to the results of multiple linear regression analysis conducted in this study, economic abuse was associated with depression, anxiety and stress. Studies conducted in Nepal 36 and Iran 37 similarly reported that elderly people who were economically abused had a higher risk of depression than others. Therefore, it has been recommended to evaluate mental health in cases of economic abuse 38 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to what is known, the majority of trending studies on geriatric depression have focused on improved diagnostic tools; 34–37 prevalence; 38–41 comprehension of differences in demographic traits (eg, occupation status, gender, age, marital status, health status, and social support); 42 and the plausible risk factors. 43–45 Consistently, researchers have found that geriatric depression can be influenced by various family factors such as family support, 46 quality of life enjoyment and satisfaction, 47 loneliness, 48 neglect, 49 and grief. 50 Our study intends to explore the influence of the family environment on geriatric depression symptoms in the Rwandan context.…”
Section: Introductionmentioning
confidence: 94%